ANALYSIS OF LANDSLIDES CAUSES ON BTS. KOTA BATU - BTS. KAB. KEDIRI ROAD - Dewi Atikah (Journal Innovation of Civil Engineering (JICE), 2021)
Landslides can occur due to decreased slope stability due to soil degradation and rock degradation making up the slopes. The problem of land mass movement occurred in the Bts. Kota Batu - Bts. Kab. Kediri Road (Link 187) Ngroto Village, Pujon District, Malang Regency, precisely at KM Mlg 31+350. This study is to determine the cause of the landslide on the Bts. Kota Batu - Bts. Kab. Kediri (Link 187) KM Mlg 31+350 and to find out the appropriate handling method to overcome the landslide. The factors causing landslides were analyzed from various sides as follows: due to existing conditions, due to changes in land use, topographic conditions, and geological conditions. The selection of the handling method, according to the situation and conditions in the field, is the use of a masonry retaining wall structure, the application of sheet piles, the handling of groundwater around the landslide area, and the normalization of rivers.